Determinants and outcome of a Clean Development Mechanism in Malaysia - Zainuddin, Z.; Zailani, S.; Govindan, K.; Iranmanesh, M.; Amran, A. (Elsevier, 2017)
The Clean Development Mechanism (CDM) enables transferring technology from developed countries to developing countries, such as Malaysia, and simultaneously promotes sustainable growth. Although this has been proven, the contribution of Malaysian companies in CDM projects is low. Therefore, this study has been aimed at investigating the determinants of CDM adoption and its impact on companies' performances. Data were gathered by surveying 91 companies in the energy, agriculture, and forestry sectors in Malaysia implementing CDM projects. The data were analysed using the partial least squares technique. The results show that environmental regulations, competitiveness, and financial benefits have a positive impact on CDM implementation. Additionally, this study reported a significant positive effect of CDM implementation on economic performance. This paper extends the knowledge on the determinants and financial outcome of CDM implementation. The information given in this research might be beneficial for policy makers and managers in modifying tactics and strategies towards successful promotion of the CDM in developing countries.